Spatio-Temporal Variation of Urban Air Quality and Its Relation with Meteorological Variables in Bangladesh (Journal of Science and Technology Research, 2026)
Particulate Matter (PM) pollution is a major environmental concern in cities of  Bangladesh due to its health impacts. The amount of pollution in the air is steadily  becoming worse in district level. The study aims to examine the relationship between  air quality and meteorological factors in Dhaka and Rajshahi, two major cities in  Bangladesh. By analyzing the concentration of PM over the land uses, the research seeks  to provide valuable insights into the urban air pollution dynamics of these rapidly growing  metropolises. Three sets of 15 minutes data (PM₁, PM₂.₅ and PM₁₀) were collected from  ground level of each location. PM₂.₅ and PM₁₀ measurements were conducted using  automated portable air quality monitor called "Aeroqual S500” and for PM₁, handheld  air quality monitor “DM106A” has been deployed. The findings reveal that Dhaka  consistently experiences higher levels of PM pollution compared to Rajshahi, indicating  poorer air quality. Comparing the land uses in both the cities the mixed areas of Dhaka  exhibit the highest concentration of all types of PM though the concentrations in all the  land uses in this city cross the standard limit while in Rajshahi the highest concentration  is found in industrial areas. The variations in PM concentrations can be attributed to  factors such as industrial activities, vehicular emissions, population density, and local  meteorological conditions (Humidity and Temperature). Additionally, the analysis of  PM₂.₅ to PM₁₀ ratio provides insights into the composition of particulate matter in the  air, highlighting the importance of understanding pollution sources and atmospheric  conditions. The study also investigates the correlation between atmospheric parameters  (humidity and temperature) and PM concentrations in both cities, revealing a negative  relationship. As humidity and temperature increases, PM₁, PM₂.₅ and PM₁₀ concentrations  tend to decrease. This underscores the influence of meteorological conditions on air  pollution levels and emphasizes the need to consider local climatic factors when designing  pollution control measures. Furthermore, the study highlights the issue of transboundary  air pollution, particularly concerning Aerosol Optical Depth (AOD). Rajshahi, situated  near the West Bengal region of India, exhibits higher AOD levels compared to Dhaka,  indicating the influence of transboundary pollution sources. Addressing this issue requires  regional cooperation, including the establishment of air quality monitoring networks,  data sharing, and coordinated strategies with neighboring countries. J. of Sci. and Tech. Res. 6(2): 97-108, 2025